Regimen-Specific Rates of Chemotherapy-Related Amenorrhea in Breast Cancer Survivors. Issue 4 (9th October 2019) - Gast, Kelly C; Cathcart-Rake, Elizabeth J; Norman, Aaron D; Eshraghi, Leah; Obidegwu, Nwamaka; Nichols, Hazel B; Rosenberg, Shoshana; Su, H Irene; Stewart, Elizabeth A; Couch, Fergus J; Vachon, Celine M; Ruddy, Kathryn J
Abstract: Young women who have not begun or completed their desired childbearing at the time of diagnosis with breast cancer often wish to understand and minimize their risk of chemotherapy-related amenorrhea (CRA). However, the incidence of CRA after regimens that do not include either an anthracycline or a cyclophosphamide is poorly studied. For patients with human epidermal growth factor receptor 2–positive disease, anthracycline- and cyclophosphamide-sparing regimens (eg, carboplatin/taxane) are common (in combination with human epidermal growth factor receptor 2–directed therapy). In this study, accrued in collaboration with Army of Women, menstrual data were analyzed for 151 breast cancer survivors (median age = 41 years at diagnosis, and median time between last chemotherapy and survey = 62.5 months). Last menstrual period was before the last chemotherapy dose in 51% of the 86 participants who received anthracycline/cyclophosphamide/taxane, in 42% of the 43 who received only taxane/cyclophosphamide, and in 13% of the 15 who received carboplatin/taxane. This study suggests that carboplatin/taxane causes less CRA than cyclophosphamide-based regimens.